A Systematic Review of Fintech and Banking Profitability - Adey Tarawneh; Aisyah Abdul-Rahman; Syajarul Imna Mohd Amin; Mohd Fahmi Ghazali (International Journal of Financial Studies, 2024)
Financial technology (Fintech), characterized as technology-driven financial innovation, has catalyzed significant economic growth across various nations. The Fintech sector has experienced remarkable expansion, boasting vast user numbers. While regions like the United States and China have seen accelerated Fintech development, other areas like Western Europe, Eastern Asia, and the Middle East continue their evolutionary journey with this technology. Our research offers a systematic review of contemporary literature, probing the crucial Fintech metrics affecting bank profitability and identifying the primary factors influencing these profits. This review introduces a holistic methodology for quantitatively assessing the evolving Fintech measures and their interplay with determinants of bank profitability. According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, our study evaluates 28 articles from Web of Science and Scopus databases from August 2019 to August 2023. Findings delineate two principal themes: Fintech measures at both bank and country levels and determinants of profitability, encompassing bank-specific and country-specific variables. We utilize the Theories, Constructs, Contexts, and Methods framework to chart the course for future research. Our insights bear significance for theoretical progression and practical implementation, offering academics, banking professionals, and policymakers a nuanced comprehension of the nexus between Fintech and bank profitability.